Effects of Different Dietary Levels of Palm Pollen (Phoenix dactylifera L.) On the Humoral Immunity and Hematology of Broiler Blood - Shihab , Ihsan Mohammed (International Journal of Poultry Science, 2018)
Background and Objective: In this study, we evaluated the effects of palm pollen (pp) added to the diet of broiler chicks on the immune response against both Newcastle disease virus (NDV) and infectious bursal disease (IBDV) and blood protein. Materials and Methods: Ninety-six 1-35-day-old chicks (Ross 308) were distributed randomly in four treatment groups, with four replicates of six chicks in each replicate. Chicks whose initial weight was 38 g were purchased from a local hatchery in the holy city of Karbala. The following treatments were used: T1 (control) birds were administered a basal diet, T2 birds were administered a 2 g kg–1 diet, T3 birds were administered a 4 g kg–1 diet and T4 birds were administered a 6 g kg–1 diet. Results: The ELISA test titer revealed significant (p